Postvaccinal Encephalitis after ChAdOx1 nCov‐19. Issue 3 (13th August 2021) - Zuhorn, Frédéric; Graf, Tilmann; Klingebiel, Randolf; Schäbitz, Wolf‐Rüdiger; Rogalewski, Andreas
Abstract : The global SARS‐CoV‐2 pandemic has contributed to more than 163 million confirmed infections and 3.3 million deaths worldwide. The severity of the pandemic has led to an unprecedented effort to develop multiple effective vaccines. Due to excellent safety and efficacy data from clinical trials, several vaccines were approved. We report a case series of postvaccinal encephalitis in temporal correlation to vaccination with ChAdOx1 nCov‐19. The diagnostic criteria for possible autoimmune encephalitis were fulfilled. Our patients responded well to immunosuppressive therapy with corticosteroids. The incidence has been estimated to be approximately 8 per 10 million vaccine doses. Complication of postvaccinal encephalitis after ChAdOx1 nCoV‐19 vaccination still appear to be very rare, but need to be diagnosed and treated adequately. Large pooled data from observational epidemiologic studies are necessary to verify causality. ANN NEUROL 2021;90:506–511